Answer:
a vertical shift of 6 units up
Step-by-step explanation:
We have the transformation:
g(x) = f(x) + k
This is what we call a vertical shift, this transformation moves the graph of f(x) k units, and the motion is upwards if k is positive, and downwards if k is negative.
Here we can see that the graph of f(x) intersects the y-axis at y = -2
While the graph of g(x) intersects the y-axis at y = 4.
Then the distance between these two points is:
4 - (-2) = 6
This means that the graph of g(x) is 6 units above the graph of f(x)
Then we have that k must be equal to 6, then the transformation is:
g(x) = f(x) + 6
This is a vertical shift of 6 units up.